A polymeric nanocarrier with a tumor acidity-activatable arginine-rich (R9) peptide for enhanced drug delivery. (4th March 2020) - Zhang, Liting; Jiang, Chengtao; Zeng, Fanjun; Zhou, Haiyu; Li, Dongdong; He, Xinyu; Shen, Song; Yang, Xianzhu; Wang, Jun
Abstract : The cell-penetrating function of R9 peptide of DA@R9 -NPDOX was masked in the blood circulation, while reactivated in tumor tissue for enhanced tumor cellular uptake. Abstract : Cell-penetrating peptides (CPPs) have been considered as a powerful tool to improve the intracellular and nuclear delivery efficiency of nanocarriers. However, their clinical application is limited because of their nonspecific targeting function, short half-life, and severe system toxicity. Herein, we have developed a polymeric nanocarrier with a tumor acidity-activatable arginine-rich (R9 ) peptide for targeted drug delivery. The nanocarrier is fabricated with a R9 -conjugated amphiphilic diblock polymer of poly(ethylene glycol) (PEG) and poly(hexyl ethylene phosphate) (PHEP), and then further coated with tumor acidity-activatable polyanionic polyphosphoester through electrostatic interaction in order to block the nonspecific targeting function of the R9 peptide. In the slightly acidic tumor extracellular environment (∼pH 6.5), tumor acidity-activatable polyanionic polyphosphoester would be deshielded from the nanoparticles, resulting in the re-exposure of the R9 peptide to enhance tumor cellular uptake. As a result, intracellular concentration of payload in 4T1 tumor cells significantly increased at pH 6.5. And, we further demonstrate that such a delivery system remarkably promoted the anti-tumor efficiency of chemotherapeutic drugs in tumor-bearing mice, offering great potential for drug delivery and cancer therapy.